The leakage study between restorative and pulp capping materials and diffusion analysis by Fick laws - Kamalak, Hakan; Demirel, Serkan; Oz, Erdinc; Altin, Serdar (Biointerface Research Applied Chemistry, 2016)
The investigation of adhesion behaviour of restorative and pulp Capping Materials in dental treatment is an important subject for the development of new maerials and prevent unwanted conditions such as secondary carriers prevelance and pain due to the leakage. The aim of the study is the development of new methods for leakage studies between the restorative and pulp capping materials. The micro-CT experiment was supported by the obtained mechanism by using Fick diffusion laws for leakage. It is found that the X-ray micro tomography analysis should be supported by the other techniques like electron microscopy and energy dispersive X-ray spectroscopy. Diffusion mechanism calculations have been identified by EDX analysis and it is found that there are two different diffusion mechanisms in the interface region between the pulp capping and the restorative materials. So the suffer duration after dental treatment is strongly dependent on the strong of inner part of the interface region.
Keywords: Leakage; Fick Law; Dental materials; Ag diffusion